Serum levels of matrix metalloproteinase-2 in patients with oral submucous fibrosis and oral squamous cell carcinoma - Kherde, Pooja; Gosavi, Suchitra (International Journal of Research in Medical Sciences, 2020)
Background: Matrix metalloproteinase-2 (MMP-2), which is supposed to enable cancer cells cross the basement membrane and metastasize by selectively cleaving type IV collagen, is anticipated to be a good diagnostic and prognostic marker in oral squamous cell carcinoma (OSCC) and oral submucous fibrosis (OSMF). Thus, the study is aimed to estimate and compare the serum MMP-2 levels in patients with OSMF and OSCC. Methods: The study was conducted on 88 subjects, divided into three groups; Group I (healthy subjects, n=28), Group II (patients with OSMF, n=30), and Group III (patients with OSCC, n=30). Serum levels of MMP-2 were estimated and compared among the groups and further with the clinical parameters within the groups. Results: The mean serum MMP-2 levels in patients with OSMF (2.87±1.04 ng/mL) and with OSCC (11.55±2.16 ng/mL) were significantly higher than the healthy subjects (0.93±0.26 ng/mL) (p <0.0001, for both). Furthermore, the mean serum MMP-2 levels in OSMF subjects had a positive association with inter-incisal opening (IIO), however, there was no association with the degree of burning sensation. Likewise, in subjects with OSCC, levels of serum MMP-2 showed positive association with histopathological grades, however, significant association with the site of occurrence and primary tumor size was not found. Conclusions: Elevated serum MMP-2 levels can be used as a screening tool in the early detection of OSMF and OSCC cases. Moreover, MMP-2 might be a good marker in evaluating the tumor grade in OSCC and the IIO in OSMF.